eScanner: uma ferramenta para validação de páginas Web segundo o e-MAG - Modelo de Acessibilidade de Governo Eletrônico - Oliveira, Victor Adriel de Jesus; Silva, Vânia Cordeiro da (Anais do Latin American Symposium on Digital Government (LASDiGov); 2012: Anais do IV Workshop de Computação Aplicada em Governo Eletrônico, 2012)
This paper describes the motivations and the development process of the tool eScanner, which is a tool for automatic validation of accessibility of Web pages according to the Electronic Government Accessibility Model - e-MAG. The eScanner was built as an extension to the Google Chrome browser and, when activated, evaluates the code of the document opened in the browser based on the recommendations of the e-MAG. Besides, it displays information about the Electronic Government Department, e-MAG and other validation tools.